Association between very advanced maternal age women with gestational diabetes mellitus and the risks of adverse infant outcomes: a cohort study from the NVSS 2014-2019 - Lin Lu; Lidan He; Jifen Hu; Jianhua Li (BMC, 2023)
Abstract Background To evaluate the association between gestational diabetes mellitus (GDM) and infant outcomes in women of very advanced maternal age (vAMA) (≥45 years). Methods This cohort study utilized data from the National Vital Statistics System (NVSS) database (2014-2019) in the United States. Preterm birth was the primary outcome, which was subdivided into extremely preterm, very preterm, and moderate or late preterm. The secondary outcomes were neonatal intensive care unit (NICU) admission, low birthweight and small for gestational age. Univariate and multivariate logistic regression analyses were used to explore the association between GDM and infant outcomes among vAMA women. Subgroup analyses were performed based on race and use of infertility treatment. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated. Results A total of 52,544 vAMA pregnant women were included. All analysis made comparisons between women with vAMA and GDM and women with vAMA and no GDM. Women with GDM had a significantly higher risk of preterm birth than those without GDM (OR = 1.26, 95%CI = 1.18-1.36, P < 0.001). Compared with women without GDM, those with GDM had a significantly increased risk of moderate or late preterm birth (OR = 1.27, 95%CI = 1.18-1.37, P < 0.001); no significant association of GDM with extremely preterm birth and very preterm birth was observed. Women with GDM had a significantly greater risk of NICU admission than those without (OR = 1.33, 95%CI = 1.23-1.43, P < 0.001). GDM was associated with a significantly lower risk of low birthweight (OR = 0.91, 95%CI = 0.84-0.98, P = 0.010), and no significant association was found between GDM and small for gestational age (OR = 0.95, 95%CI = 0.87-1.03, P = 0.200) in vAMA women. Conclusion vAMA women with GDM had an increased risk of preterm birth, especially moderate or late preterm birth. NICU admission and low birthweight were also associated with GDM among vAMA women.